Evaluation of inflammatory hyperreflective foci and plasma EPA as diagnostic and predictive markers for age-related macular degeneration - Wan, Zhongqi; Wu, Yan; Shen, Tianyi; Hu, Chengyu; Lin, Ruoyi; Ren, Chengda; Yu, Donghui; Li, Tingting; Zhu, Meijiang; Cai, Wenting; Yu, Jing (Frontiers in Neuroscience, 2024)
ObjectivesTo detect the plasma polyunsaturated fatty acids (PUFAs) concentrations in age-related macular degeneration (AMD) patients and healthy controls. Additionally, advanced studies were conducted to investigate the relationship between PUFAs concentrations and ophthalmological characteristics, including hyperreflective foci (HRF), visual acuity, and anti-vascular endothelial growth factor (anti-VEGF) response in patients with AMD.MethodsThis prospective, single-site study recruited a total of 315 participants, consisting of 105 individuals with dry AMD (early-stage AMD group), 105 individuals with neovascular AMD (late-stage AMD group), and 105 elderly individuals without any fundus diseases (healthy controls). The levels of omega-3 and omega-6 PUFAs in plasma were detected using gas chromatography. Retinal thickness, choroidal thickness, and macular volume were quantified using optical coherence tomography angiography (OCTA) scan with a 6 × 6 mm macular area, and the amounts of HRF were analyzed with OCTA scanning data.ResultsCompared to the control group, AMD patients exhibited significantly lower plasma concentrations of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) and alpha linolenic acid. HRF were observed in various retinal layers of AMD patients, particularly those with late-stage AMD. The correlation coefficient matrix and multiple linear regression models demonstrated that HRF played a crucial role in best corrected visual acuity for both early (p < 0.001) and late-stage AMD patients (p = 0.006), while EPA had an inverse effect on the logarithm of the minimum angle of resolution (logMAR) value in patients with early-stage AMD (p < 0.001). As compared to patients with good responses to anti-VEGF therapy, those with poor responses had significantly lower baseline logMAR (p < 0.001), central retina thickness (p = 0.002), macular volume (p = 0.027), HRF (p = 0.024), and plasma EPA (p < 0.001). This study used a ROC curve analysis to identify the combination of HRF and EPA as a potential biomarker for predicting the response to anti-VEGF treatment in late-stage AMD patients, with an area under the curve (AUC) value of 0.775.ConclusionsReduced plasma EPA was detected in AMD cases and the lower EPA concentration was related to poorer visual acuity. Additionally, the quantity of HRF combined with concentration of plasma EPA may serve as the prognostic indicator for predicting the effect of anti-VEGF treatment in late-stage AMD patients.